Methods of long-term planning of corporate financing - V. V. Prokhorov; I. P. Rozhnov (Вестник университета)
The questions on long-term planning of an enterprise’ bonded loan interest rate payments have been studied. The methods have been considered and the classification of methods for planning the bonds interest rate proposed. Several groups of such planning methods have been singled out. The analysis of application of bond interest rate planning methods applied by enterprises of different national industries has been made. The analysis has been carried out in the spheres of mechanical engineering, generation, transmission and sales of electric power, ferrous metals production, transportation and logistics, foodstuffs production, and information transmission provision. Corporate bond issues issued between 2015 and 2020 have been analyzed. As a result, the three methods most frequently used by enterprises in planning bond interest rates have been identified: methods of considering the macroeconomic risk of an organization; methods of considering the combination of macroeconomic and individual risk of an organization; methods based on market analysis. The study of the mentioned methods allowed us to propose a method of planning the bond interest rate, which calculates the weighted average of the forecast bond interest rate. To assess the quality of the proposed method, it has been tested. The article concludes that it can be used at enterprises planning to issue their own bonded loans.